2019
DOI: 10.3390/agronomy9120865
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation of Manure into Ridge and Furrow Planting System Boosts Yields of Maize by Optimizing Soil Moisture and Improving Photosynthesis

Abstract: A sustainable management strategy of soil fertility and cropping system is critical to guaranteeing food security. However, little is known about the effects of soil amendment strategies on crop growth via regulating soil moisture and photosynthesis in a ridge and furrow cropping system. Here, field experiments were carried out in 2017 and 2018 in semi-arid areas of Loess Plateau, northwest China to investigate the effects of integrated use of ridge and furrow planting and manure amendment on grain yields of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…These results are in line with the findings of Saraswati et al (2016) which showed that application of organic manures such as farmyard manure and poultry manure increased the availability of nitrogen, phosphorus and potassium in the soil owing to slow decomposition of the manures. In a related study, the contents of soil organic matter, total N, and total P were shown to increase by 16, 12 and 10%, respectively, after only two years of incorporating sheep manure (Qin et al, 2019). Thus, combining innovative soil management practices such as manure amendment and ridge tillage can be an efficient management strategy to improve soil chemical properties and enhance the productivity of millet in semi-arid areas of northeast Nigeria.…”
Section: Treatment Effects On Selected Soil Chemical Propertiesmentioning
confidence: 99%
“…These results are in line with the findings of Saraswati et al (2016) which showed that application of organic manures such as farmyard manure and poultry manure increased the availability of nitrogen, phosphorus and potassium in the soil owing to slow decomposition of the manures. In a related study, the contents of soil organic matter, total N, and total P were shown to increase by 16, 12 and 10%, respectively, after only two years of incorporating sheep manure (Qin et al, 2019). Thus, combining innovative soil management practices such as manure amendment and ridge tillage can be an efficient management strategy to improve soil chemical properties and enhance the productivity of millet in semi-arid areas of northeast Nigeria.…”
Section: Treatment Effects On Selected Soil Chemical Propertiesmentioning
confidence: 99%
“…SWC was measured on a dry weight basis. Soil bulk density (g cm -3 ) at the same depth and interval was determined before and after the experiment using stainless steel ring method [22]. SWC (% vol) was calculated by multiplying soil gravimetric water content with soil bulk density (g cm -3 ) from the same layer.…”
Section: Soil Water Content and Infiltration Measurementsmentioning
confidence: 99%
“…Under high bulk density of 1.5 g cm -3 , the RMSE remains 1.48% vol, and RPD is 3.7, less than the threshold value. So far, the standard oven-drying method is considered the most accurate method of SWC measurement [22]. Similarly, the weighing lysimetric method is regarded the most reliable approach to estimate crop evapotranspiration [6].…”
Section: Soil Water Content and Infiltration Measurementsmentioning
confidence: 99%
“…Averaged across the whole growing season, mean CWSI thresholds were 0.45, 0.35, 0.28, and 0.20 for I1, I2, I3, and I4 treatments. In Equation (1), field capacity was used as an indicator for the upper limit of water that can be used by plants, which was determined in the laboratory by measuring the amount of water retained at an applied pressure of -33 kPa, whereas wilting point was determined at an applied pressure of 1500 kPa [42]. In this study, the wilting point in the 0-30, 30-60, 60- After each crop sowing, all experimental plots were irrigated with 30 mm water to guarantee the uniform and rapid germination of seeds (Table 1).…”
Section: Experimental Designmentioning
confidence: 99%